Biskupi i prezbiterzy w Kościołach I i II wieku (Jerozolima, Azja Mniejsza i Grecja, Antiochia), cz. 1 - Misiarczyk, Leszek (Vox Patrum, 2024)
The article, after detailed analyses of the sources, refines M. Simonetti’s conclusions about the role of bishops and presbyters in early Christian communities of the first and second centuries. Firstly, the term πρεσβύτερος and his function appears in the communities founded by St. Paul during his lifetime, who himself established presbyters “elders” in various churches on Asia Minor so he had no resistance as Simonetti suggests to the use of terminology prevalent in Judaism. Secondly, Simonetti assumes that a monarchical episcopate is present in the Pastoral Epistles, which implies that the term πρεσβύτερος present there should be understood as the second level of the hierarchy and not as “elder”. This is not quite so obvious. One sometimes gets the impression that it still retains the meaning of “elder”. And thirdly, the reconstruction presented makes sense provided that by the term πρεσβύτεροι we mean “elders” and not the second degree of the priesthood. This, on the other hand, does not ring out unequivocally in his studies. On the other hand, if we understand the term πρεσβύτεροι to mean the second degree of the priesthood, and if the process itself proceeded in such a way that first the communities were led by colleges of priests, and then they were supplanted by a single bishop, or a monarchical episcopate emerged from among them, and the priests were relegated to the second order and to the role of associates of the bishop, then such a process is not confirmed by the first and second century sources.